The Sociodemographic Characteristics of Suicide Cases in Mersin - Metin, Ali; Çileli, Günay; Koçar, İlker; Dokgöz, Halis (The Bulletin of Legal Medicine, 2014)
Suicide may occur as a result of the imbalance in the social solidarity, dependence and autonomy relationship. Suicide act may vary according to the structure and strength of social ties. Relationship with the public and social support type influences the suicidal behavior of individuals. We determine the sociodemographic characteristics of suicidal deaths of 30 cases that occurred between 2012 and 2013 in Mersin; youngest is 15 years old girl, the eldest is 80 years old female, mean age 38.46 years, 17 (56,7 %) cases were male and 11 (36,6 %) were married, 16 (53,4 %) were single. 11 (36,6 %) cases drug and other substance intake, seven (23,3 %) hanging method, five (16,6 %) high drop method had applied. 11 (36,6 %) cases in winter and eight (26,6 %) in autumn, the suicide action has been performed. Four (13,33 %) cases previously had a history of suicide attempts, seven (23,33 %) cases previously had treated with psychiatric disorders.As for suicide, sociological, biological and psychological approaches, reveals the complexity of suicide. In this study, suicidal deaths were to determine the sociodemographic characteristics of cases in Mersin.Key words: Suicide, Autopsy, Forensic medicine, Sociodemographic characteristics, Death.
Keywords: suicide; autopsy; forensic medicine; sociodemographic characteristics; death